Syntactic Structures Constituted by Interjections in the Bulgarian Language - Малджиева, Вяра (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article is devoted to syntactic structures of Bulgarian phrases constituted by interjections. The analysis presented in the study concludes with a list of sentence and non-sentence structures with their assigned lexemes which belong to two subclasses of interjections: onomatopoeic and predicative. It also includes preliminary observations on the semantic motivation of the syntactic structures in focus.